NON-FORMAL ADULT EDUCATION IN LITHUANIA - Zemaitaityte, Irena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article reviews the regulatory legal documents for non-formal adult education and lists the diversity of institutions providing non-formal adult education. Non-formal adult education forms a large part of a permanent education system and is an active factor in stimulating Lithuanian democracy growth; it empowers individuals and social groups to deal with social, economical and political problems by advanced critical thinking and assists adults in gaining diverse approaches to tolerance. A system of non-formal education consists of training institutions, voluntary organizations, culture and education institutions, commercial establishments and groups of mutual support. Media and modern information technologies play an important role in this system. Non-formal adult education through its complexities and structural diversity develops conceptual change and behavior of the individuals in the complicated and ever changing modern world.